Genre-Based Approach To Teaching Speaking Of Descriptive Text (A Case Study At A Rural Junior High School In South West Nusa, Indonesia) - Ahmad Nahid; Muchlas Suseno; Hanip Pujiati; Juanda juanda (State Institute for Islamic Studies IAIN of Metro, 2018)
. This study aims to examine the effectiveness of Genre Based Approach in teaching students’ speaking of descriptive text and to investigate the improvement, if any, of junior high school students in their speaking of descriptive genre. To achieve those purposes, both quantitative and qualitative research were utilized. Specifically, one post-test only quasi-experimental design was chosen to achieve the first aim, while case study was utilized to answer the second research purpose. To collect the data, non-participant observations and students’ speaking test were conducted. The data from observation were then analyzed using inductive analysis while the students’ speaking test was proceed using statistical calculation through t-test and also analyzed using the genre framework analysis of descriptive text. The result reveals that GBA is effective to develop students’ speaking descriptive text and the improvement of students is seen from the social function, text organization and linguistic features of the text. Additionally, this study suggests that EFL teachers use GBA to teach other types of text. Keywords: Descriptive text,Genre Based Approach